2014
DOI: 10.1007/s10646-014-1285-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of glufosinate on nitrogen assimilation at the physiological, biochemical and molecular levels in Phaeodactylum tricornutum

Abstract: This study investigated the effects of glufosinate, a widely used herbicide, on the marine diatom Phaeodactylum tricornutum through short-term toxicity tests at the physiological and gene transcriptional levels. Glufosinate (4 mg L(-1)) decreased the amount of pigments but increased reactive oxygen species (ROS) and malondialdehyde levels. As a glutamine synthetase (GS) inhibitor, glufosinate affected the transcripts and activities of key enzymes related to nitrogen assimilation. Transcript levels of GS and ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…5). On the other hand, faster growing phytoplankton cells often need more nitrogen to synthesize more cellular enzyme that can efficiently transform the obtained inorganic substances from environments to their own cellular organic matter (Xie et al 2014), additionally indicated by the lower P:N molar ratio in the exponential phase compared to that of stationary and decay phases (Fig. 3B).…”
Section: Discussionmentioning
confidence: 99%
“…5). On the other hand, faster growing phytoplankton cells often need more nitrogen to synthesize more cellular enzyme that can efficiently transform the obtained inorganic substances from environments to their own cellular organic matter (Xie et al 2014), additionally indicated by the lower P:N molar ratio in the exponential phase compared to that of stationary and decay phases (Fig. 3B).…”
Section: Discussionmentioning
confidence: 99%
“…qRT-PCR analysis was performed on CFX96 Touch TM Deep Well Real-Time PCR Detection System (Bio-rad, America). The gene coding β-actin was selected as an internal control (Xie et al, 2014). The sequences of target genes were obtained from KEGG database 1 and primers shown in Table 1 were designed by NCBI.…”
Section: Quantitative Real Time Pcrmentioning
confidence: 99%
“…Although the effect of herbicides on NR has been studied in plants, there are not many data on this subject in microalgae, but decreases in NR due to exposure to different herbicides have been reported (Fayez & Abd-Elfattah, 2007;Prado et al, 2009). However, NR activity was not significantly affected by the herbicide glufosinate in the marine diatom Phaeodactylum tricornutm (Xie et al, 2014). Transcriptomic analyses carried out by RNA-Seq technique in C. reinhardtii cells exposed to atrazine have also shown a downregulation of NIT1 gene which encodes a nitrate reductase (Esperanza et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…The expression, stability and activity of NR are subject to complex regulations. The activation level of NR is influenced by environmental factors, including the presence of different pollutants (Mosulen et al, 2003;Lillo et al, 2004;Fayez & Abd-Elfattah, 2007;Prado et al, 2009;Xie et al, 2014). Results obtained with C. reinhardtii show that the NR activity is extremely sensitive to atrazine ( Fig.…”
Section: Discussionmentioning
confidence: 98%